Comparison of spatial‐temporal regional development and sustainable development strategy in Lithuania - Burinskienė, Marija; Rudzkienė, Vitalij (International Journal of Strategic Property Management, 2010)
Description of urban development could be explained like common endeavors of society to coordinate economical growth and social progress, to save usage of nonrenewable resources without threat of ecological balance. In the light of the attitudes of sustainable development researchers have raised the purpose to determine the current situation and possibilities of sustainable development of regions in Lithuania. Sustainable urban and regional development is closely related with investment in tangible fixed assets as well as direct foreign investment. This paper describes an approach for recognition of investment information patterns and the main factors that have a distinct impact on investment. The proposed multivariate data analysis strategy allow to evaluate, forecast and establish the favorable conditions for investment and develop the strategies for cohesive development of regions. In this article we present the application of the model using a database of economic and social development of regions in Lithuania. Our approach effectively recovers the structure of investment and enables forecasting. The capability to evaluate measurable features, identify the main features, and quantify their relationship with number of investments in space and time makes this approach applicable for decision support system and for creating range system for evaluation potency of the towns and regions. First Published Online: 18 Oct 2010